Ubuntu and Afrofeminism for Decolonizing Evaluation - Fatimata Kane; Thomas Archibald (The Evaluation Center at Western Michigan University, 2023)
Background: African evaluation has been at the forefront of innovating the praxis of decolonizing evaluation, especially through 'Made in Africa Evaluation' (MAE) and related efforts. Still, there is a wealth of additional African epistemologies and philosophical paradigms which either have not been adequately discussed in the literature, or have not yet made their way into the discourse and practice of MAE. Purpose: The purpose of this conceptual paper is to propose a theoretical framework that can be used to further inform indigenous and decolonizing evaluation approaches in African contexts and beyond. Specifically, we address the often-cited notion of ubuntu, informed by African philosophical literature beyond the field of evaluation, and we propose Sylvia Tamale's decolonizing and Afro-feminist lens as a complementary philosophical framing with great potential applications in indigenous and decolonizing evaluation in African contexts and beyond. Setting: Not applicable. Intervention: Not applicable. Research Design: This conceptual study draws on philosophical literature from African philosophy and political science to weave together notions of ubuntu with decolonizing Afro-Feminism. Data Collection and Analysis: Not applicable. Findings: We propose that a decolonizing, indigenous evaluation approach rooted in Ubuntu and Afro-Feminism would: question categorial, dichotomous, hierarchical logics (e.g., methodological hierarchical hegemonies); recognize masculinist, imperialist, modernist ideals inscribed in institutions (e.g., via government rationality, therefore also via evaluation); foreground intersectionality; and make room for "the moral economy" and other deeply communitarian framings.